2009
DOI: 10.1038/gt.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Lister strain of vaccinia virus armed with endostatin–angiostatin fusion gene as a novel therapeutic agent for human pancreatic cancer

Abstract: SummarySurvival following pancreatic cancer remains poor despite incremental advances in surgical and adjuvant therapy, and new strategies for treatment are needed. Oncolytic virotherapy is an attractive approach for cancer treatment. In this study, we have evaluated the effectiveness of the Lister vaccine strain of vaccinia virus armed with the endostatin-angiostatin fusion gene (VVhEA) as a novel therapeutic approach for pancreatic cancer. The Lister vaccine strain of vaccinia virus was effective against all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 48 publications
1
60
0
Order By: Relevance
“…3 It was shown that the oncolytic adenovirus expressing a human endostatin and angiostatin fusion protein (hEA) imposed potent antiangiogenic effects and suppressed the prostate tumor growth in mouse models, 4 while the vaccinia virus expressing hEA also delayed the pancreatic cancer progression. 5 However, these vectors possess respective drawbacks. 3,6 For instance, adenovirus mounts potent immune responses while the packaging capacity of AAV is limited.…”
Section: Introductionmentioning
confidence: 99%
“…3 It was shown that the oncolytic adenovirus expressing a human endostatin and angiostatin fusion protein (hEA) imposed potent antiangiogenic effects and suppressed the prostate tumor growth in mouse models, 4 while the vaccinia virus expressing hEA also delayed the pancreatic cancer progression. 5 However, these vectors possess respective drawbacks. 3,6 For instance, adenovirus mounts potent immune responses while the packaging capacity of AAV is limited.…”
Section: Introductionmentioning
confidence: 99%
“…These trials have indicated the inherent safety of the virus, efficacy of intravenous delivery of VV, VV infection of metastatic deposits, and reproducible disease control in many patients enrolled in the trials. However, along with other groups (9), we have observed that there is variability in cell killing by VV in different cancer cell lines, and the reasons for this are not fully understood (10).…”
mentioning
confidence: 68%
“…The statistical analysis was conducted using one-way ANOVA. *, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. ing vaccine strains, have been shown to inherently target tumors (10,35). This tumor selectivity is partially attributed to the activation of the epidermal growth factor/Ras-MEK-extracellular signal-regulated kinase (ERK) pathways and deregulation of interferon (IFN) pathways in cancer cells (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, limited progress has been achieved in this field. To improve and replace combinational therapy, modifying anti-angiogenesis gene by genetic engineering to create novel fusion gene with higher activity, more powerful function and stability is receiving more and more attentions (19,20). ENDO-VEGI 151 is a novel anti-angiogenesis gene from our laboratory (4,5,21,22).…”
Section: Discussionmentioning
confidence: 99%